All Names Are Not Equal: Choice of Marital Surname and Equal Protection - Kelly Snyder (Washington University Journal of Law & Policy, 2009)
Part I of this Note recounts the history of women‘s lack of autonomy in marriage, the history of marital name-change, and the establishment of intermediate scrutiny as the constitutional test under which gender-based equal protection issues are analyzed. Part II of this Note analyzes the lack of men‘s statutory right in most states to change their last names upon marriage through the lens of intermediate scrutiny and concludes that there is an equal protection violation. Part II further analyzes why a majority of marrying women adopt their husbands‘ surnames, and asserts that marrying men‘s relative inability to change their surnames has the negative effect of further restricting women‘s agency, in that the "choice" marrying women have in changing their surnames resembles more of a coerced decision. Part III of this Note reviews statutes of the eight states in which men possess a statutory right to change their last names upon marriage, and proposes that all states adopt similar statutes that not only grant marrying men and women the same processes for changing their last names, but also eliminate the discriminatory language found in existing statutes.
Keywords: Name changes; Marriage; Equal rights; Equal protection; Married women; Personal names